Occurrence of the green aIga Trentepohlia on the trunk and branches of durian - Lim, Tong Kwee; Sijam, Kamaruzaman (Incorporated Society of Planters, 1989)

(untitled)
Three green alga species viz. Trentepohlia aurea, T. arborum and T. monile were identified forming thick, felty incrustation on the bark of trunks and primary lateral brandies of durian trees, Tile pathological implications of such algal growth 011 durian are examined and discussed.